Current Guidelines on Management of Amaurosis Fugax and Transient Ischemic Attacks. Issue 2 (23rd March 2022) - Mbonde, Amir A.; O'Carroll, Cumara B.; Dulamea, Octaviana A.; Anghel, Daniela; Chong, Brian W.; Dumitrascu, Oana M.
Abstract : Abstract: Transient ischemic attack (TIA) is defined as a transient episode of neurological dysfunction resulting from focal brain, spinal cord, or retinal ischemia, without associated infarction. Consequently, a TIA encompasses amaurosis fugax (AF) that is a term used to denote momentary visual loss from transient retinal ischemia. In this review, we use the word TIA to refer to both cerebral TIAs (occurring in the brain) and AF (occurring in the retina). We summarize the key components of a comprehensive evaluation and management of patients presenting with cerebral and retinal TIA. All TIAs should be treated as medical emergencies, as they may herald permanent disabling visual loss and devastating hemispheric or vertebrobasilar ischemic stroke. Patients with suspected TIA should be expeditiously evaluated in the same manner as those with an acute stroke. This should include a detailed history and examination followed by specific diagnostic studies. Imaging of the brain and extracranial and intracranial blood vessels forms the cornerstone of diagnostic workup of TIA. Cardiac investigations and serum studies to evaluate for etiological risk factors are also recommended. The management of all TIAs, whether cerebral or retinal, is similar and should focus on stroke prevention strategies, which we have categorized into general and specific measures. General measures include the initiation of appropriate antiplatelet therapy, encouraging a healthy lifestyle, and managing traditional risk factors, such as hypertension, dyslipidemia, and diabetes. Specific management measures require the identification of a specific TIA etiology, such as moderate-severe (greater than 50% of stenosis) symptomatic extracranial large vessel or intracranial steno-occlusive atherosclerotic disease, aortic arch atherosclerosis, and atrial fibrillation.